CHARACTERIZATION OF TARWI (Lupinus mutabilis Sweet) PRODUCTION UNITS - Amelia Wite Huaringa-Joaquin; Sady García-Bendezú; Rember Pinedo-Taco; Félix Camarena-Mayta (Tropical and Subtropical Agroecosystems, 2023)
Background. Tarwi is a legume native to the Andes of South America and is currently an important crop in subsistence agricultural systems because it contributes to the generation of economic income and food security for the rural population. Objetive. To characterize the tarwi production units (UPT) in the inter-Andean valleys of the department of Ancash, Peru. Methodology. The research was of a descriptive, comparative, correlational, non-experimental type, survey data from 169 UPT were used and the characterization was carried out using statistical techniques of multidimensional analysis. Implications. The UPT are small-scale, they are integrated into diversified production systems, which implies knowing their characteristics in order to define coherent development plans or projects to promote the production and consumption of tarwi. Conclusions. The UPT are family farming; the family participates in running the plots and in generating economic income both from the main crop, as well as from other complementary sources. The farmers are typified mostly as small-scale, and their production is oriented towards family food security and some surpluses for the market; however, due to the gradual loss of conservation agricultural practices, abandonment of the state in promoting its conservation, cultivation, consumption and lack of financing and technical assistance, the cultivated area of tarwi is gradually decreasing.